Global Tax Trends and Transformations: A Literature Review on Change and Adaptation - Annisa, Neng Nur; Nandy, Debasish (Jurnal Perpajakan dan Keuangan Publik, 2024)
This study aims to explore and analyze trends and transformations in the global tax system by referring to the latest literature studies. In the context of an ever-evolving economy and rapid globalization, tax systems in various countries are undergoing significant changes to respond to new challenges and adaptation needs. This study conducts a comprehensive literature review covering various aspects, including tax policy reform, the impact of digitalization on the tax system, and the application of new technologies in tax administration. Through an analytical approach, this study identifies key patterns in global tax transformation, such as the shift from traditional to digital-based taxation, and international efforts to address tax avoidance and profit shifting. This study also highlights the adaptation of tax systems in developing countries compared to developed countries, as well as the challenges and opportunities faced by each. The results of this study are expected to provide deeper insights into the dynamics of change in the global tax system and offer recommendations for policymakers, academics, and tax practitioners in formulating more effective and adaptive strategies and policies in the future.